Impact of type 2 diabetes mellitus on the prognosis of patients with hepatocellular carcinoma after laparoscopic liver resection: A multicenter retrospective study - Yang, Shi-Ye; Yan, Mao-Lin; Feng, Jin-Kai; Duan, Yun-Fei; Ye, Jia-Zhou; Liu, Zong-Han; Guo, Lei; Xue, Jie; Shi, Jie; Lau, Wan Yee; Cheng, Shu-Qun; Guo, Wei-Xing (Frontiers in Oncology, 2022)
Background: The effect of type 2 diabetes mellitus (T2DM) on survival of patients with hepatocellular carcinoma (HCC) after laparoscopic liver resection (LLR) has not been reported. This study aimed to explore the relationship between preoperative T2DM and long-term prognosis in HCC patients undergoing LLR. Methods: HCC patients receiving LLR as initial treatment at four cancer centers were retrospectively included in this study. Clinicopathological factors associated with the prognosis of HCC patients were identified using univariate and multivariate Cox regression analysis. Recurrence-free survival (RFS) and overall survival (OS) curves between different cohorts of patients were generated using the Kaplan-Meier method and compared using the log-rank test. Results: Of 402 HCC patients included, 62 patients had T2DM and 340 patients did not have T2DM. The OS and RFS of patients with T2DM were significantly worse compared to those without T2DM (P = 0.001 and 0.032, respectively). In Cox multivariate analysis, T2DM was identified as an independent risk factors for OS (HR = 2.31, 95% CI = 1.38–3.85, P = 0.001) and RFS (HR = 1.66, 95% CI = 1.08–2.55, P = 0.020). Conclusions: Following laparoscopic surgical approach, HCC patients with T2DM had poorer prognoses than those without T2DM. Preoperative T2DM was an independent risk factor for HCC patients. Thus, patients with concurrent HCC and T2DM should be closely monitored after LLR.